Effects of salidroside on rat CYP enzymes by a cocktail of probe drugs - Wei, Yan-Li (Iran J Basic Med Sci, 2018)
OBJECTIVE(S): In this study, we aimed to evaluate the effect of salidroside on the activities of the different drug-metabolizing enzymes CYP1A2, CYP2B6, CYP2C9, CYP2D6 and CYP3A4 in rats, in which a specific probe drug was used for each enzyme. MATERIALS AND METHODS: After pretreatment with salidroside, five probe drugs were simultaneously administered to rats by gavage. The given dose was 2.0 mg/kg for phenacetin (CYP1A2 activity), 4.0 mg/kg for bupropion (CYP2B6 activity), 2.0 mg/kg for losartan (CYP2C9 activity), 8.0 mg/kg for metoprolol (CYP2D6 activity) and 1.0 mg/kg for midazolam (CYP3A4 activity). Then, an ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to analyze the concentrations of rats’ blood, which were collected at different corresponding times. RESULTS: Our data showed that salidroside exhibited an inductive effect on CYP1A2, CYP2B6, CYP2C9 and CYP3A4 activities by changing the main pharmacokinetic parameters (t1/2, CL/F, Cmax and AUC(0-∞)) of the four probe drugs in rats. However, no significant changes in CYP2D6 activity were observed. CONCLUSION: In a word, the results displayed that salidroside could induce the activities of CYP1A2, CYP2B6, CYP2C9 and CYP3A4, which may influence the disposition of the drugs that are mainly metabolized by these pathways. Our research can provide the basis for the study of related herb-drug interactions in clinic.